2017
DOI: 10.1111/tmi.12845
|View full text |Cite
|
Sign up to set email alerts
|

How do low‐birthweight neonates fare 2 years after discharge from a low‐technology neonatal care unit in a rural district hospital in Burundi?

Abstract: Abstractobjectives As neonatal care is being scaled up in economically poor settings, there is a need to know more on post-hospital discharge and longer-term outcomes. Of particular interest are mortality, prevalence of developmental impairments and malnutrition, all known to be worse in lowbirthweight neonates (LBW, <2500 g). Getting a better handle on these parameters might justify and guide support interventions. Two years after hospital discharge, we thus assessed: mortality, developmental impairments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…As expected, there was higher burden of stunting, underweight, and wasting (58.8%, 47.5%, 25.8%, respectively) among children enrolled in the PDC aged 6–59 months between 2014 and 2017, compared to the national prevalence of undernutrition among children under five years of age in rural Rwanda (stunting: 40.6%, underweight: 10.0% and wasting: 2.3%) [ 8 ]. Two earlier studies in Rwanda and Burundi showed elevated rates of stunting, underweight and wasting among preterm and LBW infants, however stunting in our sample was lower (58.8% in PDC versus 79.0% in Rwanda without PDC at ages 12–36 months and 81.0% in Burundi at age 2 years) and prevalence of wasting was higher (25.8% PDC versus 9.0% and 18.0%, respectively) [ 9 22 ]. It is important to note that both of these studies had a large number of children that could not be located for assessment (23–46%) or died (4–6%) indicating potential survival bias which might explain the lower overall wasting prevalence given that the children lost to follow-up had characteristics that put them at high risk for wasting and death [ 23 ].…”
Section: Discussioncontrasting
confidence: 77%
“…As expected, there was higher burden of stunting, underweight, and wasting (58.8%, 47.5%, 25.8%, respectively) among children enrolled in the PDC aged 6–59 months between 2014 and 2017, compared to the national prevalence of undernutrition among children under five years of age in rural Rwanda (stunting: 40.6%, underweight: 10.0% and wasting: 2.3%) [ 8 ]. Two earlier studies in Rwanda and Burundi showed elevated rates of stunting, underweight and wasting among preterm and LBW infants, however stunting in our sample was lower (58.8% in PDC versus 79.0% in Rwanda without PDC at ages 12–36 months and 81.0% in Burundi at age 2 years) and prevalence of wasting was higher (25.8% PDC versus 9.0% and 18.0%, respectively) [ 9 22 ]. It is important to note that both of these studies had a large number of children that could not be located for assessment (23–46%) or died (4–6%) indicating potential survival bias which might explain the lower overall wasting prevalence given that the children lost to follow-up had characteristics that put them at high risk for wasting and death [ 23 ].…”
Section: Discussioncontrasting
confidence: 77%
“…We found significantly higher rates of developmental delay at 2–3 years of age among infants born preterm and/or LBW. This increase in developmental delay was also seen in neighboring Burundi, where 27% of LBW children had some form of developmental impairment based on a screening questionnaire at age two after discharge from a neonatal care unit [37]. In Malawi, infants born preterm were more likely to screen positive for disability on a parent-reported assessment tool and had higher rates of developmental delay at 18 months compared to term infants (22.8% versus 10.9%) [38].…”
Section: Discussionmentioning
confidence: 83%
“…Letaiefin Tunis found that the rate of low birth weight is higher among mothers aged under 18 years [11]. Advanced maternal age has been shown in many countries as a risk factor for low birth weight [20] [23]. This was also confirmed by Mabiala Bibela JR-Brazzaville who found that maternal age is often linked to low birth weight with higher risk in adolescents and in women aged over 35 years [10].…”
Section: Discussionmentioning
confidence: 84%
“…It was not found, as studies conducted in Senegal [18] and Morocco [19] a significant link between the number of antenatal care and low birth weight. A recent study in several developing countries has shown that inadequate prenatal care was among the least significant risk factors for the most important birth [20]. It should be noted that prenatal care is very bad in the Guinean population studied.…”
Section: Discussionmentioning
confidence: 87%